STUDENT LEARNING STYLE OF MATHEMATICS EDUCATION BASED ON GENDER - Farman, Farman (IJBLE Scientific Publications Community Inc., 2023)
This study aimed to identify and describe the learning modalities of students in mathematics education based on gender. This research is a type of quantitative research that uses a descriptive design. The research was conducted at the Mathematics Education Study Program, USN Kolaka. The population in this study were all students of the mathematics education class 2018, totalling 40 students. The sampling technique in this study used non-probability sampling in the form of saturated sampling. The instrument used in this study was a questionnaire containing statements used to obtain research information about visual (V), auditory (A), read/write (R), and kinesthetic (K) learning modalities, which are called VARK. The data analysis technique in this study used descriptive analysis based on the trend analysis of learning modalities. This trend data is then described in the form of tables and graphs. The results showed that the 2018 USN Kolaka Mathematics Education Study Program students' learning styles had a multimodal preference. Male students have a preference for multimodal learning style in bimodal (AR and AK) as 5 (41.66%) of 12 students. On the other hand, female students tend towards a multimodal learning style in bimodal (AR), as much as 6 (21.4%) of 28 students.